2013
DOI: 10.4103/2278-330x.110487
|View full text |Cite
|
Sign up to set email alerts
|

Does the cancer patient want to know? Results from a study in an Indian tertiary cancer center

Abstract: Objective:The disclosure of the diagnosis of cancer is a distressing and complex issue. Families and doctors still do not tell patients when they have cancer in the belief that the patient does not want to know and telling him would lead to fear and depression. The aim of this survey was to evaluate the information needs of Indian cancer patients.Materials and Methods:A cross-sectional survey of 300 patients’ views was conducted with the help of an adaptation of Cassileth's Information Needs questionnaire.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 42 publications
4
14
1
Order By: Relevance
“…The authors concluded that most of the patients wanted to know about their illness and treatment, and the desire for information is significantly greater among younger patients, literate patients, and those receiving treatment with a curative intent. 5 Although the majority of our patients had a lower level of education, we found that most of them desired to know about their illness and treatment.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The authors concluded that most of the patients wanted to know about their illness and treatment, and the desire for information is significantly greater among younger patients, literate patients, and those receiving treatment with a curative intent. 5 Although the majority of our patients had a lower level of education, we found that most of them desired to know about their illness and treatment.…”
Section: Discussionmentioning
confidence: 72%
“…Although there are many studies done in the West to assess the information needs of the patients with cancer, there has only been one such study done in India. 5 The results of that study indicate a significant association between the age of the patient, level of education, and type of treatment with their information needs. The authors concluded that most of the patients wanted to know about their illness and treatment, and the desire for information is significantly greater among younger patients, literate patients, and those receiving treatment with a curative intent.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The need for information about the diagnosis and treatment of cancer was expressed by 94% of the patients with cancer, and 92% wanted information about the prognosis, as revealed in a study by Laxmi and Khan. 17 However, awareness about the disease leads to increased psychiatric morbidity among patients with cancer in India. 18 Per the notification of the Medical Council of India on the Code of Medical Ethics Regulations, 2002, it is essential to disclose the diagnosis and prognosis to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, prior research has indicated that patients with advanced cancer from LMICs preferred to know their prognosis at much higher rates—60% of patients in Pakistan, 29 92% of patients in Brazil, 30 79% of patients in China, 28 and 92% of patients in India. 31 Given these findings, it is important to determine and accommodate patient preferences regarding prognostic information individually, as South African patients may tend to prefer not knowing their prognosis.…”
Section: Discussionmentioning
confidence: 99%